Ketekunan Spiritual: Kompetensi Karakter Pelayan Tuhan dalam Narasi 2 Timotus 1:1-18 - Jonatan Ivan Jemy Lawa; Sutikto Sutikto (KHARISMATA: Jurnal Teologi Pantekosta, 2024)
Problems and challenges as a servant of God are things that always happen, many of which become withdrawn and do not act as expected. This problem can be a difficult challenge for anyone who is specifically called to serve God. This article uses qualitative methods to expose verse 2 Timothy 1:1-18, arguing this research for the importance of God's servants building a theology of perseverance as saints in carrying out their ministry duties. focuses on Paul's advice to Timothy to persevere as a constructive point in building pastoral theology. The aim of the research is to understand the socio-psychological context of Timothy and the situation of the church in Ephesus, explore the theological message, and highlight the challenges of Timothy's ministry. Findings show that perseverance in ministry is a key element, expressed through Paul's admonitions, with analysis of the Biblical text identifying the characteristics of God's servants. The results of the research include understanding the call to ministry, Timothy's specific challenges, and the importance of perseverance in the success of God's ministry. This article significantly enriches theological and practical understanding regarding Christian ministry, encouraging further reflection on the integration of the principles of 2 Timothy in the context of modern church ministry. Tantangan sebagai pelayan Tuhan bukan masalah biasa, banyak diantaranya menjadi mundur dan tidak berperan sesuai harapan. Masalah ini bisa menjadi tantangan yang berat bagi siapapun yang terpanggil khusus melayani Tuhan. Artikel ini menggunakan metode kualitatif untuk mengeksposisi ayat 2 Timotius 1:1-18, argumentasi penelitian ini pentingnya pelayan Allah membangun teologi ketekunan sebagai orang-orang kudus dalam menjalani tugas pelayanan. fokus pada nasehat-nasehat Paulus kepada Timotius untuk bertekun menjadi titik konstruktif membangun teologi pastoral. Tujuan penelitian adalah memahami konteks sosio-psikologis Timotius dan situasi gereja di Efesus, mengeksplorasi pesan teologis, serta menyoroti tantangan pelayanan Timotius. Temuan menunjukkan bahwa ketekunan dalam pelayanan adalah elemen kunci, diungkapkan melalui nasihat-nasehat Paulus, dengan analisis teks Alkitab mengidentifikasi karakteristik pelayan Tuhan. Hasil penelitian mencakup pemahaman panggilan pelayanan, tantangan spesifik Timotius, dan pentingnya ketekunan dalam kesuksesan pelayanan Tuhan. Penelitian ini memberi kontribusi signifikan untuk memperkaya pemahaman teologis dan praktis terkait pelayanan kristiani, mendorong refleksi lebih lanjut tentang integrasi prinsip-prinsip 2 Timotius dalam konteks pelayanan gereja modern.